Pd-Catalyzed Decarboxylative Couplings of Aryl Triazine Esters With Zinc Polyfluorobenzoates - Du, Hong-Jian; Yin, Hao-Nan; Zhou, Yun; Chu, Xue-Qiang; Xu, Hao; Shen, Zhi-Liang (Synthesis, 2025)
A Pd-catalyzed decarboxylative cross-coupling using zinc polyfluorobenzoates as robust polyfluoroarylating agents and aryl triazine esters as effective benzoylating reagents was realized, enabling the facile assembly of a wide array of valuable polyfluorinated aryl ketones in moderate to good yields. A variety of functional groups could be well tolerated in the protocol, and the reaction could be scaled up as well. Especially noteworthy is that one-pot reaction by directly adding polyfluorobenzoic acid and Zn(OH)2 to the decarboxylative reaction as a precursor to in situ form zinc polyfluorobenzoate could also be successfully achieved, thereby providing a more practical, step-economic, and cost-effective approach for accessing polyfluorinated aryl ketones. Control experiments showed that zinc pentafluorobenzoate was superior to other metallic counterparts.
Keywords: Palladium catalysis; Decarboxylative reaction; Zinc polyfluorobenzoate; Aryl triazine ester; Polyfluorinated aryl ketone